2013
DOI: 10.1161/circep.113.000102
|View full text |Cite
|
Sign up to set email alerts
|

Left Cardiac Sympathetic Denervation in Long QT Syndrome

Abstract: Background-Long QT syndrome (LQTS) is a potentially lethal but highly treatable cardiac channelopathy. Treatment options include pharmacotherapy, device therapy, and left cardiac sympathetic denervation (LCSD). Here, we sought to determine the characteristics of LQTS patients who have had ≥1 LQTS-related breakthrough cardiac event (BCE) after LCSD. Methods and Results-We performed retrospective chart review for 52 consecutive patients (24 males; mean age at diagnosis, 10.0±10 years; mean QTc, 528±74 ms) with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 23 publications
3
68
1
Order By: Relevance
“…Several centers have reported their experience with LCSD for LQTS and CPVT. [11][12][13][14][15][16] The rate of side effects in these studies is not as high as the current authors report. However, prevention of arrhythmia is not the only indication for sympathetic denervation.…”
Section: Article See P 1151contrasting
confidence: 51%
“…Several centers have reported their experience with LCSD for LQTS and CPVT. [11][12][13][14][15][16] The rate of side effects in these studies is not as high as the current authors report. However, prevention of arrhythmia is not the only indication for sympathetic denervation.…”
Section: Article See P 1151contrasting
confidence: 51%
“…They proposed that LCSD should be considered for patients with recurrent syncope episodes under maximal pharmacological treatment and for patients who suffer arrhythmia storms in the presence of an ICD. More studies have emerged following that paper, but in the majority of them some 20 to 50% of the patients do remain symptomatic having had LCSD (15)(16)(17)(18)(19)(20)(21)(22) and there are also studies that identified that almost 50% of high-risk patients may experience more than one cardiac event post LCSD (14,20). Atallah et al (17) described that four patients with LQTS underwent VATS LCSD.…”
Section: Mini-reviewmentioning
confidence: 99%
“…Indeed, it is both, a safe and effective treatment option to reduce life-threatening ventricular arrhythmias in patients with heritable channelopathies such as LQTS. A prophylactic LCSD, rather than a prophylactic ICD, may represent a good treatment option for patients with unacceptable b-blocker-related side effects [41]. In contrast, a stellate ganglion blockade on the right side significantly prolongs the QT interval while the QT dispersion increases.…”
Section: The Effect Of Regional Anaesthesia Techniques On the Period mentioning
confidence: 99%